ANALISIS BUNDARAN JALAN ARTERI SUPADIO DAN JALAN MAYOR ALIANYANG - Jamanda, Firdaus; AS, Syafaruddin; ., Sumiyattinah (JeLAST : Jurnal PWK, Laut, Sipil, Tambang, 2016)
The crossing is part of a network of roads that need to be arranged in such a way so as to reduce the conflicts that frequently occurs at every intersection. United States in the meeting of Supadio Arterial and Major Alianyang road which is the intersection of a piece in the shaper of the roundabout.The survey methods used to 'obtain primary data with observational techniques  provide that became the object of study. The Equipment which is used in the primary data capture i. e : Hand tally counter, a survey form letter, gauge and wrist. Secondary data collection using the method of documentary study that is how data collection is done with the category and classification of written material relating to research issues. While the method of calculation using the Indonesia Manual calculation of the road capacity satwa Braided Gravel . The results of the analysis capacity calculation of the existing conditions at the Supadio Arterial and Major Alianyang road in 2015 gained the greatest Degree of Saturation value (DS) 0.744. By using the method of trial and error from the data, the number of for military and comercial purpose by 2015, then obtained a degree intersection design which is saturation is lower than on existing conditions, the united states well as the addition of the islands dividing the value of the Degree of Saturation (DS).  And the results of the analysis --: 0.657 < 0.85 Key words : Crossroads Strip, The Survey Methods, Degrees of Saturation